Crystal structure of poly[hexaqua-pentakis(μ4-2,2′-bipyridine-4,4′-dicarboxylato-κ4 O:O′:O″:O‴)-(μ2-2,2′-bipyridine-4,4′-dicarboxylato-κ2 O:O)tetraytterbium(III)] hydrate, C36H26N6O16Yb2 - Cheng Zheng; Zhang Xiao-Yu; Liu Xu; Yang Xiao-rui (Zeitschrift für Kristallographie - New Crystal Structures)
C36H26N6O16Yb2, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 11.3387(3) Å, b = 12.1820(4) Å, c = 14.1433(4) Å, α = 95.090(2)°, β = 103.517(3)°, γ = 101.762(2)°, V = 1840.41(10) Å3, Z = 2, Rgt (F) = 0.0282, wRref (F 2) = 0.0576, T = 150 K.